Exploring of the property of epoxy resins based on diselenide and disulfide dynamic linkers - Wei, Xiao; Liu, Feng; Guo, Xinru; Gao, Fei; Li, Yingjia; Zhu, Dongtao; Zhou, Zhi; Shen, Liang (Frontiers in Chemistry, 2022)
Over the last decade, there has been a lot of interest in incorporating dynamic covalent bonds (DCBs) into epoxy resins. Because diselenide and disulfide bonds have similar properties, they are frequently used as DCBs in self-healing epoxy networks. In this paper, we present diselenide and disulfide dynamic linkers containing epoxy networks by analyzing the effects of mechanical properties, thermal stability, activation energies, and self-healing properties. The glass transition temperature (Tg) values, mechanical properties, crosslinking density (ve), and thermal stability of disulfide linkers networks were higher than those of diselenide linkers networks, according to our research. The activation energies of disulfide linkers were higher than those of diselenide linkers (up to 14 kJ/mol), but their healing efficiency was lower than that of the diselenide network. These findings demonstrate the advantages of diselenide and disulfide dynamic linkers in epoxy networks systems, as well as a method for designing and preparing the appropriate diselenide dynamic linkers or disulfide dynamic linkers incorporated into epoxy networks for the appropriate application and processing technology.